ANALISIS QUALITY OF SERVICE JARINGAN INTERNET PADA UNIVERSITAS DAYANU IKHSANUDDIN - Nur, Jabal; Israwan, LM. Fajar; Saputra, Maulana (Informatics Engineering Department, Dayanu Ikhsanuddin University, 2022)
Quality of service or quality of performance on the internet network of Dayanu Ikhsnaudiin University (Unidayan) needs to be maintained in good performance as one of the requirements for the formation of an integrated digital system. The purpose of this research is to measure the quality and service of the internet network at Unidayan so that it can determine the level of satisfaction of users using the network. The test method used in this study uses a quantitative analysis method by monitoring the internet network to measure throughput, delay, jitter and packet lost parameters at the access point which is determined as a sample in each building using the wireshark software. From the results of the research conducted, it can be concluded that the quality of service of the internet network at Dayanu Ikhsanuddin University is included in the Moderate category according to TIPHON with a percentage of 50% -74.75%.